Crumpling for energy: modeling generated power from the crumpling of polymer piezoelectric foils for wearable electronics. (14th August 2017) - Kodali, P; Saravanavel, G; Sambandan, S
Abstract: We consider the possibility of embedding large sheets of polymer piezoelectrics in clothing for sensing and energy harvesting for wearable electronic applications. Power is generated by the crumpling of clothes due to human body movements. From the mechanics of a gently crumpled foil, we develop theoretical models and scaling laws for the open circuit voltage and short circuit current and verify these via experiments. It is concluded that stretching is the dominant charge generation mechanism with the open circuit voltage and short circuit current proportional to l i and l i − 1 ( d l / d t ), respectively with 1 ≤ i ≤ 4 / 3 and l the height of the crumple cone.